Disaster Awareness and Preparedness and Disaster Risk Reduction Practices among Secondary Schools - J. Arcegono, Winda; Alma V. Olorga; Mercedes B. Sumandal (Yayasan Nurul Yakin Bunga Tanjung, 2024)
Inevitable disasters pose a concealed threat that school leaders must address to prevent calamity and safeguard lives and assets. This study determined the disaster risk reduction awareness in selected secondary schools, aiming to mitigate current risks and enhance the resilience of vulnerable institutions. This study uses a quantitative approach. The research employed online surveys to gauge disaster risk reduction management among 50 secondary school heads and teachers in Northern Puerto Princesa City, Philippines. The findings revealed a high level of awareness among respondents, highlighting the importance of implementing programs like budget allocation for DRRM activities, student-led hazard mapping, and collaboration with local government units and NGOs. In conclusion, strengthening disaster risk reduction management and fostering partnerships are recommended for secondary schools to enhance preparedness and resilience.